Environmental Ethics in Ali Yafie`S Perspective and Its Significance for Environmental Conservation in Indonesia - Fathurahman, M.; Suryaningsih, Ruliq (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The real environmental problems are not just a problem of garbage, pollution, illegal logging, burning of forests and so on, but it is already in the field of human life point of view. Thus, the environmental problem actually comes from the mindset and egocentric attitude of humans in seeing themselves and their surroundings. The human self needs with all its aspects then fulfilling by sacrificing the environment is precisely the essence of the environmental problem itself. If that happens, then the problem might not be finished by curative actions (restoration, reforestation, etc.). Therefore, putting environmental ethics as a solution is the right thing. This is because environmental ethics includes not only technical issues, but also provides awareness that environmental damage is not only physically harmful but it is actually morally harmful. Hence, there are areas that are considered more crucial than the occurrence of environmental problems, namely aspects of morality. So that providing learning about environmental ethics is considered more principle and effective in reducing environmental problems